Mass spectrometry in food proteomics: a tutorial. (September 2014) - Cunsolo, V.; Muccilli, V.; Saletti, R.; Foti, S.; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> In this tutorial special feature, Dr Vincenzo Cunsolo and colleagues are introducing the readers to the characterization by MS‐based approaches of food‐derived proteins. Knowledge of protein composition is helpful for understanding the relationship between the protein content and the nutritional and technological properties of foodstuff, the production of methods for food traceability, the assessment of food quality and safety or even for the detection of genetically modified products and microbial contaminants. Moreover, considering that most of the more consumed foods (e.g. milk, eggs, cereals etc.) are responsible of allergenic reactions in humans, the detection of allergenic proteins represents a hot topic in the food safety field, because it may contribute to provide the basis for the production of hypoallergenics or to develop nutraceutical foods. Dr Cunsolo is a researcher of organic chemistry at the University of Catania. His research activity is mainly devoted to the structural characterization of food proteins, more specifically from kernel cereals and milk, by MS‐based proteomics methods. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>